Aeolian surface transformations on the alluvial fan of the Nyírség - Lóki, József; Négyesi, Gábor; Buró, Botond; Félegyházi, Enikő (Journal of Environmental Geography, 2012)
The evolution of the Nyírség and its landforms has been widely addressed by Hungarian geographers and geologists in the past and at present as well. Early works were mainly concentrating on understanding the complex, fluvial and aeolian genetics of the territory, later more specific forms and problems were studied and revealed. By the increasing number of chronological evidence derived from stratigraphic, pollen and archaeological data and absolute dating techniques (radiocarbon and optically stimulated luminescence) the geomorphological development can be reconstructed in more detail, especially in the context of climate variations and human intervention. Our study aims to summarize and outline the times of aeolian activity, with special respect to Holocene events, on the basis of the researches carried out so far. By nowadays it is obvious that sand was moving on several occasions in the Nyírség during the Holocene subsequent to the main aeolian land formation periods of the Upper Pleniglacial and the late glacial. In the first half of the Holocene sand movement can be related to dry periods, thus aeolian activity was driven mostly by climatic factors. In the second half of the Holocene the area of land affected by wind erosion decreased and in most cases events can be associated to the activity of man. Nevertheless, climatic and anthropogenic factors could be superimposed, leading to significant local sand mobilisation.